2019
DOI: 10.1186/s12984-019-0632-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supraspinal feedback on human gait: rhythmic auditory distortion

Abstract: BackgroundDifferent types of sound cues have been used to adapt the human gait rhythm. We investigated whether young healthy volunteers followed subliminal metronome rhythm changes during gait.MethodsTwenty-two healthy adults walked at constant speed on a treadmill following a metronome sound cue (period 566 msec). The metronome rhythm was then either increased or decreased, without informing the subjects, at 1 msec increments or decrements to reach, respectively, a low (596 msec) or a high frequency (536 msec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Therapy satisfaction has recently been shown by Wang et al (2021) to be higher when music-based stimulation is used [ 41 ]. In order to maintain the metronome rhythm, gait speed is adapted subconsciously but Forner-Cornero et al (2019) found that the relation between the foot contact and the sound cue showed a mean error which increased when frequencies changed [ 42 ]. When frequencies changes from baseline, the foot contact tend to be before the sound cue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapy satisfaction has recently been shown by Wang et al (2021) to be higher when music-based stimulation is used [ 41 ]. In order to maintain the metronome rhythm, gait speed is adapted subconsciously but Forner-Cornero et al (2019) found that the relation between the foot contact and the sound cue showed a mean error which increased when frequencies changed [ 42 ]. When frequencies changes from baseline, the foot contact tend to be before the sound cue.…”
Section: Discussionmentioning
confidence: 99%
“…When frequencies changes from baseline, the foot contact tend to be before the sound cue. Forner-Cornero suggested that two processes might be involved in rhythm entrainment, one a slow-adapting, supraspinal oscillator, which predicts the foot contact, and a second fast process related to sensory inputs, which adapts peripheral sensory input (foot contact) and supraspinal sensory input (auditory rhythm) [ 42 ]. Studies into supraspinal feedback errors with a music-based rhythmic auditory stimulation should be planned in future research.…”
Section: Discussionmentioning
confidence: 99%
“…When the RAC frequency increases, the asynchrony between the stimulus and response decreases because the response is usually “advanced” with respect to the stimulus. On the other hand, when the RAC frequency decreases, the asynchrony increases 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the subliminal RAC changes could be used to “probe” the gait control system under sleep deprivation. We employed this unique paradigm that we previously developed 34 to provide a basic RAC at a given frequency and then applied the changes of increasing and decreasing frequencies at very small increments (1 ms). The rhythm is maintained for a time interval before returning to the original RAC frequency.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, one proposed approach has been to exploit the sensorimotor synchronization paradigm ( Repp, 2005 ; Torre et al, 2010 ), which evaluates a subject’s ability to match the rhythmic oscillations of a limb with an external (often auditory) stimulus, including infrequent temporal perturbations (where beats are presented earlier or later than expected). This paradigm therefore challenges the individual’s inherent rhythmicity during walking and assesses the elicited adaptive motor responses ( Chen et al, 2006 ; Roerdink et al, 2009 ; Pelton et al, 2010 ; Wagner et al, 2016 ; Forner-Cordero et al, 2019 ). The methodology has, in essence, several positive aspects: the effect of altering rhythms on walking behavior can provide controlled and reproducible access to non-steady-state behavior as encountered in the real-world (e.g., walking on uneven terrains, negotiating obstacles, etc.).…”
Section: Introductionmentioning
confidence: 99%